Beneficial health effects of milk and fermented dairy products--review - Ebringer, L; Ferencík, M; Krajcovic, J (Folia microbiologica, 2008)
Milk is a complex physiological liquid that simultaneously provides nutrients and bioactive components that facilitate the successful postnatal adaptation of the newborn infant by stimulating cellular growth and digestive maturation, the establishment of symbiotic microflora, and the development of gut-associated lymphoid tissues. The number, the potency, and the importance of bioactive compounds in milk and especially in fermented milk products are probably greater than previously thought. They include certain vitamins, specific proteins, bioactive peptides, oligosaccharides, organic (including fatty) acids. Some of them are normal milk components, others emerge during digestive or fermentation processes. Fermented dairy products and probiotic bacteria decrease the absorption of cholesterol. Whey proteins, medium-chain fatty acids and in particular calcium and other minerals may contribute to the beneficial effect of dairy food on body fat and body mass. There has been growing evidence of the role that dairy proteins play in the regulation of satiety, food intake and obesity-related metabolic disorders. Milk proteins, peptides, probiotic lactic acid bacteria, calcium and other minerals can significantly reduce blood pressure. Milk fat contains a number of components having functional properties. Sphingolipids and their active metabolites may exert antimicrobial effects either directly or upon digestion.
Keywords: zdraví; Milk; Dairy Products; Fermentation; mléko; Infant, Newborn; Health; mateřské mléko; novorozenec; zvířata; mléčné výrobky; Humans; Food; potraviny; fermentace; lidé; Milk, Human; Animals